SYUKUR: SEBUAH KONSEP PSIKOLOGI INDIGENOUS ISLAMI - Putra, Johan Satria (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2014)
Western psychology studies call the concept of thankfulness as ?gratitude?. However, gratitude itself doesn?t relevant when involved in the study of islamic psychology. The number of study using construct of ?syukur? purely based on islamic psychology is also rare. Then, this study aim to formulate theoritical concept about ?syukur? from the perspective of islamic indigenous psychology. The study used qualitative approach using grounded theory method. The participants are 41 students from the faculty of Islamic Religion in Unisma Bekasi. Each participant is given a questionnaire with one empirical question above their description about gratitude. Data analysis used coding technique, which purposed to find the dimentions that build the construct of ?syukur? in the islamic indigenous psychology context. The result show that ?syukur? consist of the acceptance of whatever that given by Allah, which the acceptance based on meaning and happiness. The feeling of thankfulness enforce individu to carry out a prosocial behavior, giving thanks by oral and action, changing him or herself, that may form a subjective well-being.